The Taj: an architectural marvel of an epitome of love? - Islam, Arshad (2010)
On Saturday 7 July 2007, the New Seven Wonders Foundation, Switzerland, in its new ranking again declared the Taj Mahal as one of the Seven Wonders of the World. Taj Mahal of India is not just an architectural feat and an icon of luminous splendor but an epitome of enormous love as well. The Mughal Emperor Shahjahan (1592-1666) got built the Taj Mahal, the fabulous mausoleum (rauza) in the memory of his beloved queen Mumtaz Mahal (1593-1631). Perhaps, there is no better and grander monument built in the history of human civilization dedicated to love. The contemporary Mughal sources refer to this marvel as rauza-i-munavvara (The illuminated Tomb). Taj Mahal of Agra, originally called Taj Bibi-ka- Rauza. It is believed that the name "Taj Mahal" was derived from the name of Mumtaz Mahal, which means the "Crown Palace". The pristine purity of the white marble, the exquisite ornamentation, precious gemstones used and its picturesque location, all make Taj Mahal a marvel of art. Standing majestically at the southern bank on the River Yamuna, it is synonymous with love and beauty. This paper highlights the architectural design and beauty of the Taj, and Shahjahan’s dedicated love for his beloved wife that led to its construction.